Análise das apresentações da performance através do público - Abdalla, Jonath Boeta; Oliveira, Pablo Vinícius Barreto de; Coutinho, Ângela Maria da Costa e Silva (Universidade de São Paulo | Escola de Comunicações e Artes, 2019)
This paper aims to analyze on the performance "Nada Poderá Tornarmos Menos Pretos Que Somos", a passage referring to the song "Paz, Coroas e Tronos" by the black singer / rap and LGBT+ Rico Dalasam, whose aim is to show through poetic art, music, corporal expression and struggle against racism, as well as seeking to value the history and knowledges of Brazil's black population, its processes of resistance, its pains, the lack of receptivity and all the adversities suffered through time , by triggering relevant aspects of culture, roots and ancestry. In this way, the performance constitutes a self-affirmation and a means of recognition of the black, points to the lack of evolution of rights since the abolition and the incessant search for self-valorization.